In Situ Growth of Three‐Dimensional MXene/Metal–Organic Framework Composites for High‐Performance Supercapacitors - Liu, Chunli; Bai, Yang; Li, Wenting; Yang, Feiyu; Zhang, Guangxun; Pang, Huan (Angewandte Chemie International Edition, 2022)
In this study, we propose a versatile method for synthesizing uniform three‐dimensional (3D) metal carbides, nitrides, and carbonitrides (MXenes)/metal–organic frameworks (MOFs) composites (Ti3C2TX/Cu‐BTC, Ti3C2TX/Fe,Co‐PBA, Ti3C2TX/ZIF‐8, and Ti3C2TX/ZIF‐67) that combine the advantages of MOFs and MXenes to enhance stability and improve conductivity. Subsequently, 3D hollow Ti3C2TX/ZIF‐67/CoV2O6 composites with excellent electron‐ and ion‐transport properties derived from Ti3C2TX/ZIF‐67 were synthesized. The specific capacitance of the Ti3C2TX/ZIF‐67/CoV2O6 electrode was 285.5 F g−1, which is much higher than that of the ZIF‐67 and Ti3C2TX/ZIF‐67 electrode. This study opens a new avenue for the design and synthesis of MXene/MOF composites and complex hollow structures with tailorable structures and compositions for various applications. A general method for synthesizing uniform 3D MXene/MOF composites was proposed. The metal ions cross‐linked with the surface termination groups of Ti3C2TX nanosheets, which destroyed the electrostatic repulsion between the nanosheets, and thereafter became the nucleation site for the in situ growth of MOF particles on Ti3C2TX nanosheets. The composites combined the advantages of MOF and MXene to enhance stability and improve conductivity.